Ameliorative Effects of Osthole on Experimental Renal Fibrosis in vivo and in vitro by Inhibiting IL-11/ERK1/2 Signaling - Fan Wu; Yan Zhao; Qingqing Shao; Ke Fang; Ruolan Dong; Shujun Jiang; Fuer Lu; Jinlong Luo; Guang Chen (Frontiers Media S.A., 2021)
Objectives: Natural product, osthole, has been proven to have a protective effect on organ fibrosis, including renal fibrosis. All of these studies are mainly focused on the regulation of TGF-β/Smad signaling pathway. However, due to the pleiotropic roles of TGF-β/Smad signaling, direct TGF-β-targeted treatments are unlikely to be therapeutically feasible in clinic. Recently, the downstream IL-11/ERK1/2 signaling of TGF-β has become an attractive therapeutic target without upstream disadvantages. Based on that, this study was designed to identify the potential effects of osthole on IL-11/ERK1/2 signaling pathway in renal fibrosis.Methods: The renal fibrosis model was established in vivo and in vitro, we investigated the effects of osthole on unilateral ureteral obstruction (UUO)-induced renal fibrosis and TGF-β-induced HK-2 cells. After preliminarily confirming the antifibrogenic effects of osthole and the link between its antifibrogenic effects and the inhibition of IL-11/ERK1/2 signaling, we applied a direct IL-11-induced HK-2 cells fibrosis model to further explore the inhibitory effects of osthole on IL-11/ERK1/2 signaling pathway.Results: Our results confirmed that osthole can decrease the secretion of fibrosis proteins, such as α-smooth muscle actin (α-SMA), collagen I, and fibronectin, ameliorate experimental renal fibrosis in vivo and in vitro, and the effect was associated with suppressing TGF-β1/Smad signaling. More importantly, we found that IL-11/ERK1/2 signaling in UUO-induced renal fibrosis and TGF-β-induced HK-2 cell model was obviously upregulated, and osthole treatment also significantly inhibited the abnormal IL-11/ERK1/2 signaling activation. Given the direct link between TGF-β/Smad signaling and IL-11/ERK1/2 signaling pathway, we have verified that osthole has a direct inhibitory effect on IL-11/ERK1/2 signaling independent of TGF-β signaling by using an IL-11-induced HK-2 cells fibrosis model. Osthole treatment decreased the protein expression of α-SMA, collagen I and fibronectin without changing their mRNA levels in IL-11-induced HK-2 cells. Moreover, it was observed that the IL-11/ERK1/2 inhibitor, U0126, partly blocked the antifibrogenic effects of osthole.Conclusion: In this study, we found that osthole has a previously unrecognized role in inhibiting IL-11/ERK1/2 signaling pathway. Our work demonstrated that the antifibrogenic effect of osthole is not only mediated by TGF-β/Smad2/3 signaling, but also directly mediated by IL-11/ERK1/2 signaling pathway independent of TGF-β1 signaling.